(untitled) (Management and Connections Journal, 2023)
The organizational ties of outsourced workers are multiple, inserted in a complex chain of relationships. On the one hand, there is the formal bond with the contracting organization, which is far from their daily work experience; and on the other, with the company for which the service is provided, where its activities are developed. This research sought to understand how the formation processes of organizational bonds occur: commitment, entrenchment and consent from the perception of organizational support of outsourced workers at the Federal University of Pernambuco. In a qualitative perspective, the results point to the understanding that only the satisfaction, albeit low, of hygienic factors is insufficient to strengthen the bonds between organization and individual, nor to guarantee the perception of support on the part of organizations, especially when dealing with outsourced individuals, implying direct reflections on their work and their experience within the organizational environment.